(untitled) (Milan Law Review, 2022)
The work examines the conflicts that can arise between the right to know one’s origins and the mother’s right to give birth anonymously, furthermore, it describes the legislative and jurisprudential developments on the issue. After a thorough analysis of the status of filiation and its evolution within the Italian legal system, it focuses on the different methods of ascertaining the status of a child both within and outside of marriage. There is attention drawn to the institution of anonymous childbirth, its reason and origins. The post-medieval institution of the so-called ’wheel of exposition’ is mentioned, as is that of modern ’cradles for life’. In conclusion, the child’s right to know his or her origins is examined, as interpreted by the most recent national and supranational case law, also following the well-known Godelli judgment of the European Court of Human Rights. It also deals with the question of the reversibility or otherwise of the mother’s secrecy on her identity after her death and in the event of her incapacity, as well as that of the possibility given to the child to make the so-called ’interpellation’ in order for the mother to revoke her declaration of not wishing to be named.